2019
DOI: 10.1039/c9ra07545c
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the deactivation mechanism of V2O5-WO3/TiO2 catalyst during selective catalytic reduction of NO with NH3: synergies between arsenic and potassium species

Abstract: Synergies between arsenic (As) and potassium (K) species in the deactivation of V2O5-WO3/TiO2 catalyst were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Synergistic mechanism of arsenic and potassium poisoning. This figure was reprinted with permission from ref . Copyright 2019 Royal Society of Chemistry.…”
Section: Mechanism Of Alkali Metal Poisoning On Scr Catalystmentioning
confidence: 99%
“…Synergistic mechanism of arsenic and potassium poisoning. This figure was reprinted with permission from ref . Copyright 2019 Royal Society of Chemistry.…”
Section: Mechanism Of Alkali Metal Poisoning On Scr Catalystmentioning
confidence: 99%
“…Synergetic poisoning effect of arsenic with potassium was evaluated in [185,186]. Results indicated that the coeffect of As + K was more dramatic than the additive effect of a single poison.…”
Section: Arsenic Poisoningmentioning
confidence: 99%
“…Two new peaks appeared at 940.5 and 1116.3 cm –1 at 25 and 40 °C; the former was assigned to the presence of As–O from the arsenic oxide product, 35 and the latter was assigned to the bonds of the Lewis (L) acid sites. 36 O 2 may participate in the chemical adsorption of hydrogen arsenide by adsorbing at L acid sites on the surface of Cu/Ac to convert to O β . 33 This indicated that a chemical adsorption process mainly occurred on the Cu/AC surface when the reaction temperature was 25 and 40 °C.…”
Section: Resultsmentioning
confidence: 99%